PAMBAGIAN KERJA BURUH PANGLONG ARANG DI DESA TANJUNG KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Muhammad Fahmi (Nusantara Hasana Journal, 2024)
The aim of this research is to look at the background of the Akit people who choose jobs as laborers in Panglong Arang and to see the pattern of work and determination of wages between male and female workers in Panglong Arang. This research was conducted using qualitative research methods, the techniques used in data collection were in-depth interviews, observation, and documentation. The subjects in this study were selected as many as 12 informants consisting of men and women and 1 person namely Panglong Arang krani. The data analysis techniques used in this study consisted of data reduction, data presentation, and drawing conclusions. The results of the study show that the reason people choose to work as laborers in Panglong Arang is because they are invited, the work is hereditary, the location is close to where they live, they have experience, and the skills and requirements are easy.Working patterns, working hours between male and female workers have relatively the same working hours. The part of the work done by women can be done by men. Whereas, the part of the work done by men is absent without the involvement of women. Determination of wages between male and female workers in Panglong Arang is seen from the workload between male and female workers. Then, the risk of work between male and female workers. Furthermore, the determination of wages is also seen from the performance and work time carried out by male and female workers.